Identification of coronary plaque rupture or erosion by preprocedural computed tomography angiography in patients with non-st-segment elevation acute coronary syndrome. (3rd October 2022) - Nagamine, T; Hoshino, M; Matsuda, K; Misawa, T; Sugiyama, T; Sasano, T; Sayama, S; Ueno, H; Hada, M; Yonetsu, T; Kakuta, T
Abstract: Background: The frequent pathological cause of acute coronary thrombosis is plaque rupture or erosion. A previous CT angiographic study failed to discriminate OCT-defined intact fibrous cap culprit lesions (IFC lesions) from those with ruptured fibrous cap (RFC group) in patients with acute coronary syndrome (ACS) and chronic coronary syndrome. Objectives: This study aimed to evaluate the diagnostic efficacy of preprocedural coronary CT imaging to identify optical coherence tomography (OCT)-defined plaque rupture or erosion at culprit lesions in patients with non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: Consecutive patients with suspected NSTE-ACS who underwent preprocedural non-contrast CT and CT angiography (CCTA) were studied. Patients with at least one lesion with more than 50% stenosis at the proximal segment on CCTA were subsequently assessed by invasive coronary angiography and OCT. ALL CT and OCT examination were performed within 24 hours from presentation. The diagnosis of intact fibrous cap or ruptured fibrous cap was made by OCT for the angiographically most severely stenosed lesion. Cases of ambiguous OCT diagnosis such as massive thrombosis or calcified nodule precluding the fibrous cap assessment were excluded from the final analysis. Results: In the final analysis of 176 patients, OCT identified 87 RFC plaques and 89 IFC plaques for the culprit lesions, respectively. In IFC group, lower prevalence of diabetes mellitus (24.7% vs. 41.4%, P=0.025) and lower peak cardiac marker elevation (CPK, 159 vs. 272 U/L, P<0.001) were observed. On CT, the prevalence of low attenuation plaque, positive remodeling, napkin ring sign, spotty calcification, calcium score (CAC), and culprit vessel pericoronary adipose tissue attenuation (FAI) were all significantly low in IFC group. Multivariate regression analysis to predict IFC at culprit lesions revealed that the absence of low attenuation plaque, the absence of napkin ring sign, zero CAC, and low FAI were independent predictors of IFC. When stratified by the number of these 4 CT factors, the presence of IFC were stratified as 0%, 23.6%, 50%, 77.8%, and 100% (P<0.001), respectively. Adding non-contrast CT factor of zero CAC to the reference model including age, sex, DM, EF, low attenuation plaque, napkin ring sign, and FAI, can increase the incremental discriminatory and reclassification performance for the prediction of IFC (C-statistic 0.828 NRI: 0.37, 95% CI: 0.095–0.646, P=0.008 and IDI: 0.042, 95% CI: 0.012–0.071, P=0.005). Conclusions: Preprocedural comprehensive CT imaging including CAC and pericoronary adipose tissue inflammation could identify IFC or RFC culprit lesions defined by OCT. Further studies are needed to confirm our preliminary results and if CT imaging in NSTE-ACS provides prognostic information or specific therapeutic approach such as conservative therapy or non-stenting strategy before invasive angiography. Funding Acknowledgement: Type of funding sources: None.